Expression of NF-κB associated lncRNAs in schizophrenia - Safa, Amin; Badrlou, Elham; Arsang-Jang, Shahram; Sayad, Arezou; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Scientific reports, 2020)
NF-κB signaling pathway has important roles in the regulation of growth and development of nervous system. This pathway has also been shown to participate in the pathogenesis of schizophrenia. Meanwhile, activity of NF-κB signaling pathway is regulated by several factors including non-coding RNAs (lncRNAs). In the current study, we evaluated expression of nine NF-κB-related lncRNAs namely DILC , ANRIL , PACER , CHAST , ADINR , DICER1-AS1 , HNF1A-AS1 , H19 and NKILA as well as two mRNA coding genes namely ATG5 and CEBPA in the peripheral blood of patients with schizophrenia compared with matched healthy subjects. Expressions of these genes were assessed by real time PCR technique. Expression of PACER was lower in patients with schizophrenia compared with controls (Posterior beta = − 0.684, P value = 0.049). On the other hand, expressions of CHAST , CEBPA , H19 , HNF1A-AS1 and DICER1-AS1 were higher in patients compared with controls (Posterior beta = 0.39, P value = 0.005; Posterior beta = 0.844, P value < 0.0001; Posterior beta = 0.467, P value < 0.0001; Posterior beta = 1.107, P value = 0.005; Posterior beta = 0.176, P value = 0.044, respectively). We also appraised the diagnostic power of transcript quantities of CHAST , CEBPA , DICER1-AS1 , H19 and HNF1A-AS1 in distinguishing between patients with schizophrenia and controls through depicting ROC curves. Based on the area under curve (AUC) values, CEBPA had the best diagnostic power (AUC = 0.948, P < 0.0001), followed by H19 (AUC = 0.815, P < 0.0001). Taken together, our study demonstrated dysregulation of NF-κB-related lncRNAs and genes in the peripheral blood of patients with schizophrenia and their potential as peripheral markers for this psychiatric condition.